A Preliminary inquiry into the Information Experiences of Canada's Wireless Consumers - Cavanagh, Mary; Pavlovic, Marina (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2018)
This paper reports on one phase of a larger telecommunications consumer rights and access - to - justice project framed by Canada's Wireless Code of Conduct (2014). Two pilot studies involving 12 mystery shopper interactions, and 16 qualitative interviews of wireless consumers are reported. Preliminary findings suggest ways the consumer’s perspective in Canada’s wireless services, legal and informational, ecology could be strengthened.